Activity deprivation induces neuronal cell death: mediation by tissue-type plasminogen activator. - Eldi Schonfeld-Dado; Menahem Segal (PLoS ONE, 2011)
Spontaneous activity is an essential attribute of neuronal networks and plays a critical role in their development and maintenance. Upon blockade of activity with tetrodotoxin (TTX), neurons degenerate slowly and die in a manner resembling neurodegenerative diseases-induced neuronal cell death. The molecular cascade leading to this type of slow cell death is not entirely clear. Primary post-natal cortical neurons were exposed to TTX for up to two weeks, followed by molecular, biochemical and immunefluorescence analysis. The expression of the neuronal marker, neuron specific enolase (NSE), was down-regulated, as expected, but surprisingly, there was a concomitant and striking elevation in expression of tissue-type plasminogen activator (tPA). Immunofluorescence analysis indicated that tPA was highly elevated inside affected neurons. Transfection of an endogenous tPA inhibitor, plasminogen activator inhibitor-1 (PAI-1), protected the TTX-exposed neurons from dying. These results indicate that tPA is a pivotal player in slowly progressing activity deprivation-induced neurodegeneration.